Using eggshell membranes as a DNA source for population genetic research - Trimbos, Krijn Baptist; Broekman, Joyce; Kentie, Rosemarie; Musters, Cees J. M.; de Snoo, Geert R. (Journal of Ornithology, 2009)
In the context of population genetic research, a faster and less invasive method of DNA sampling would allow large-scale assessments of genetic diversity and genetic differentiation with the help of volunteer observers. The aim of this study was to investigate the usefulness of eggshell membranes as a DNA source for population genetic research, by addressing eggshell membrane DNA quality, degeneration and cross-contamination. To this end, a comparison was made with blood-derived DNA samples. We have demonstrated 100% successful DNA extraction from post-hatched Black-tailed Godwit (Limosa limosa) eggshell membranes as well as from blood samples. Using 11 microsatellite loci, DNA amplification success was 99.1% for eggshell membranes and 97.7% for blood samples. Genetic information within eggshell membrane DNA in comparison to blood DNA was not affected (F(ST) = -0.01735, P = 0.999) by degeneration or possible cross-contamination. Furthermore, neither degeneration nor cross-contamination was apparent in total genotypic comparison of eggshell membrane DNA and blood sample DNA. Our research clearly illustrates that eggshell membranes can be used for population genetic research.